Responsabilidad social educativa de los directivos y la educación inclusiva en las instituciones educativas públicas del nivel secundario del distrito de Belén 2022 - Barrera Sommo de Mosquera, Paula Mercedes (2024)
The aim of this research was to determine the relationship between the educational social responsibility of school leaders and inclusive education in public secondary institutions in the district of Belen 2022. The study was a descriptive correlational type with a non-experimental cross-sectional design. The study population was composed of 188 individuals with a sample of 127 secondary school teachers in the district of Belen. The technique used was the survey and its instrument the questionnaire. There were submitted to expert judgment for validity testing, achieving an average score of 67 points, that is, within the “Very Good" range. The internal consistency was 91.70% and 93.50% for the instruments in the Cronbach's Alpha, resulting in a very high reliability. The results showed that the mean scores for the educational social responsibility variable of school leaders were 60.71, falling into the satisfactory category. The institutional commitment and community commitment dimensions obtained an average of 63.87 and 60.45, respectively, also achieving the satisfactory category. The compliance with norms and socially responsible service dimensions obtained an average of 58.87 and 58.49, respectively, falling into the normal category. The inclusive education variable and the dimensions of developing inclusive policies and practices were in the normal category due to their mean scores of 55.67, 54.24, and 51.53, respectively. The dimension of creating inclusive cultures obtained a satisfactory category with an average of 63.48. In conclusion, the educational social responsibility variable and the socially responsible service, institutional commitment, and community commitment dimensions have a high positive relationship with inclusive education (rho=0.747, 0.643, 0.715, 0.633), while the compliance with norms dimension has a moderate positive relationship with inclusive education (rho=0.560).